Pelatihan Pembuatan Nata De Leri Sebagai Pemanfaatan Limbah Air Cucian Beras - Rosa, Friska Octavia (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Indonesia is included in the top 10 countries with the highest level of rice consumption in the world. The amount of rice consumed causes the used rice washing water to be wasted and rarely used because it has no economic value. Water used for rice washing that is disposed of for free contains organic compounds and minerals that are useful for the human body, one of which is carbohydrates. The high carbohydrate content in the water used for rice washing meets the requirements for the growth of Acetobacter xylinum bacteria that can be used in making nata. Nata de leri utilizes fermented rice laundry water using other additives such as ZA (Ammonium Sulfate), granulated sugar, and kitchen vinegar. Indonesian people usually use nata as dessert or can also be used as canned food mixed with other fresh fruits. Rice washing water that is used by reprocessing is expected to create economic value and potentially bring profits. Community Service (PKM) lecturers of the Science Education Postgraduate program at Muhammadiyah Metro University are carried out to increase the capacity of the community in processing through an understanding of making nata de leri using used rice washing water.